2014
DOI: 10.1590/s0100-06832014000600009
|View full text |Cite
|
Sign up to set email alerts
|

Limite crítico no solo para transpiração e crescimento foliar em mandioca em dois períodos com deficiência hídrica

Abstract: RESUMO A cultura da mandioca geralmente é exposta a mais de um período de deficiência hídrica durante a estação de crescimento. O objetivo deste trabalho foi verificar se há diferença na Fração de Água Transpirável do Solo (FATS) crítica para transpiração e crescimento foliar em plantas de mandioca submetidas a um e dois períodos de deficiência hídrica no solo. Foram conduzidos dois experimentos com a cultura da mandioca, cultivar Fepagro RS 13. Os tratamentos foram quatro regimes hídricos subdivididos em dois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Water-deficient plants subjected to high temperatures use stomatal closure control to increase soil water use efficiency. This and other studies make clear that phytotechnical variables related to plant growth generally correlate with transpiration (PINHEIRO et al, 2014;OULEDALI et al, 2018).…”
Section: Resultssupporting
confidence: 61%
“…Water-deficient plants subjected to high temperatures use stomatal closure control to increase soil water use efficiency. This and other studies make clear that phytotechnical variables related to plant growth generally correlate with transpiration (PINHEIRO et al, 2014;OULEDALI et al, 2018).…”
Section: Resultssupporting
confidence: 61%
“…A study on the critical limits of soil moisture for the cassava crop showed that water stress significantly reduces the total leaf area of cassava plants due to lower diffusion of CO 2 by the stomata, which remain closed for a longer period (Pinheiro et al, 2014). In contrast, greater soil water availability favours plant development and increases the area for interception of solar radiation for photosynthesis and production of photoassimilates that are used for starch accumulation in the roots (Tironi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The plants that received irrigation levels of 73.09 mm had about two times more leaves than plants that received only 42.15 mm. Pinheiro et al (2014) found that total leaf area was lower in plants with water deficiency mainly due to a reduction in development of new leaves and an increase in senescence. Above the irrigation level of 73.09 mm there was no significant increase in the number of leaves, and above 104.3 mm a tendency towards reduction was observed.…”
Section: Resultsmentioning
confidence: 99%
“…As plantas que receberam 73,09 mm emitiram cerca de duas vezes mais folhas do que as plantas que receberam 42,15 mm. Em trabalho desenvolvido por Pinheiro et al (2014), a área foliar total foi inferior nas plantas com deficiência hídrica devido principalmente à redução da emissão de novas folhas e ao aumento da senescência. Acima da lâmina de 73,09 mm não houve incremento significativo, além disso, a partir da lâmina de 104,3 mm, observou-se uma tendência de redução.…”
Section: Resultsunclassified